Governance and Performance of Education Systems - Soguel, Nils C.; Jaccard, Pierre (Springer Netherlands : Imprint: Springer, 2008)
Education has increasingly become the focus of public discourse and policy, with its methods, resources and achievements widely debated. As a result, educational systems are now more than ever faced with the challenge of improving their performance and of proving that suitable measures are being taken to guarantee greater efficiency regarding equity. This desire for better results requires that better methods for their measurement exist so that they can be better understood and, ultimately, improved. Several disciplines have already developed instruments for this purpose. The educational sciences have been particularly active in this field. Other disciplines, such as sociology, economics, management, information technology, and political science are also making significant contributions to the emergence of a better form of governance. Before one can benefit from these developments, one first must know about their existence and analyse and question them. The proposed book is unique in that it brings together a wide range of disciplines and experience from several countries. What are possible models of governance? How do we measure their effects in terms of efficiency and equity? What type of contribution can financial and information systems make? How do we adapt the prevailing culture to the challenge of better performance? These are some of the concrete questions to which this book provides an answer.